Factors predicting eHealth literacy: A profile of California, USA - Ronald W. Berkowsky; Brandon Almanza; Jasmine Garcia; Noah Graza (PEC Innovation, 2025)
Objective: Given the known benefits of enhanced eHealth literacy in promoting patient health, identifying segments of the patient population at risk for low eHealth literacy can provide avenues for health professionals to promote enhanced eHealth skills through targeted outreach and intervention. The purpose of this study was to examine factors associated with eHealth literacy and to identify disparities in eHealth literacy in California. Methods: Using survey data from the 2020 CALSPEAKS survey, ordinary least squares regression was performed on measures of self-assessed eHealth literacy to identify associated factors (N = 780). Results: Findings showed that the strongest and most consistent predictors of eHealth literacy included self-rated health, a proxy measure for religiosity, Internet use characteristics, and personality traits (i.e., conscientiousness, neuroticism). Conclusion: Overall, Californians report relatively high levels of eHealth literacy – but, those seeking to increase eHealth literacy among patients in the state may benefit from tailoring digital health information and eHealth interventions based on the significant associations found. Innovation: Few studies have examined the impacts of personality characteristics on eHealth literacy using a large sample – findings elucidate innovative pathways to enhancing eHealth literacy (e.g., accommodating online content or training interventions to those reporting low conscientiousness or high neuroticism).